UJI KEMAMPUAN Trichoderma harzianum DALAM MENGHAMBAT PERTUMBUHAN Fusarium oxysporum PENYEBAB PENYAKIT LAYU TANAMAN PEPAYA (Carica papaya L) SECARA IN â VITRO - Anggrayeni, Betti; Advinda, Linda; Fifendy, Mades (STKIP PGRI Sumbar, 2014)
Â ABSTRACTÂ Â Â Fusarium is the soil born pathogens fungi that cause withered disease in host plant. Fusarium can be hold in ground longtime, because it can be klamidospora. This fungi attack the water carrier network, so that it can Â be disturb the transportation of host plant water. So the plant be withered, turn yellow and dwarf. The grow of fungi can be blocked by using biological agents, it is Trichoderma harzianum. The purpose of this research is follow to know T. harzianum ability in blocked the grow of F. oxysporum cause withered disease of papaya plants as In - Vitro. This research use RAL (The design of random completly) by 3 treatments. That consist of : (1) T. harzianum isolate 1, (2) T. harzianum isolate2, (3) T. harzianum isolate 3. The result of this research is analyzed by using Anova experiment (Analisis of Varians). The avarege of percentage result in the blocked treatment A = (60,63 %), treatment B = (51,36 %), treatment C = (65,27%). The average of colony diameter T. harzianum of treatment A = (7,53 mm), treatment B = (7,15 mm), treatment C = (8,17 mm). The average of colony diameter F. oxysporum of treatment A = (2,99 mm), treatment B = (3,18 mm), treatment C = (2,70 mm). It can be counlude that T. harzianum can blocked the grow of F. oxysporum cause of withered disease in pepaya plant (Carica papaya L) as In â Vitro.